Epigenetic regulation: The interface between prenatal and early‐life exposure and asthma susceptibility. (9th December 2013) - de, Mariàngels; Lovinsky‐Desir, Stephanie; Miller, Rachel L.; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Asthma is a complex disease with genetic and environmental influences and emerging evidence suggests that epigenetic regulation is also a major contributor. Here, we focus on the developing paradigm that epigenetic dysregulation in asthma and allergy may start as early as in utero following several environmental exposures. We summarize the pathways important to the allergic immune response that are epigenetically regulated, the key environmental exposures associated with epigenetic changes in asthma genes, and newly identified epigenetic biomarkers that have been linked to clinical asthma. We conclude with a brief discussion about the potential to apply newly developing technologies in epigenetics to the diagnosis and treatment of asthma and allergy. The inherent plasticity of epigenetic regulation following environmental exposures offers opportunities for prevention using environmental remediation, measuring novel biomarkers for early identification of those at risk, and applying advances in pharmaco‐epigenetics to tailor medical therapies that maximize efficacy of treatment. 'Precision Medicine' in asthma and allergy is arriving. As the field advances this may involve an individually tailored approach to the prevention, early detection, and treatment of disease based on the knowledge of an individual's epigenetic profile. Environ. Mol. Mutagen. 55:231–243, 2014. © 2013 Wiley Periodicals, Inc.